2016
DOI: 10.1097/mca.0000000000000322
|View full text |Cite
|
Sign up to set email alerts
|

Altered expression of lysosomal hydrolase, acid α-glucosidase, gene in coronary artery disease

Abstract: Compared with controls, GAA gene expression levels in CAD patients were significantly increased, suggesting that GAA may be involved in the CAD development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 31 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…The CBX gene family, a recent research interest in the field of long noncoding RNAs, has been associated with CVD and atherosclerosis in multiple studies [25,26]. GAA gene expression has been found to be specifically increased in CAD patients than in controls [27]. CARD14, which is mainly associated with psoriasis (ongoing clinical studies suggest increased risk of CVDs in psoriasis) and auto-inflammatory disorders, acts as a pro-inflammatory gene by affecting NF-kB activation in the IL-17 inflammation pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The CBX gene family, a recent research interest in the field of long noncoding RNAs, has been associated with CVD and atherosclerosis in multiple studies [25,26]. GAA gene expression has been found to be specifically increased in CAD patients than in controls [27]. CARD14, which is mainly associated with psoriasis (ongoing clinical studies suggest increased risk of CVDs in psoriasis) and auto-inflammatory disorders, acts as a pro-inflammatory gene by affecting NF-kB activation in the IL-17 inflammation pathway.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been found that aberrant expression of hsa-miR-139-5p could lead to apoptosis [ 26 ] which has been observed in coronary atherosclerosis [ 27 ]. hsa-miR-502-5p has been reported to inhibit autophage [ 28 ] and the alteration of autophagic genes has also be discovered in CAD [ 29 ]. So, these three miRNAs could play an important role in CAD.…”
Section: Discussionmentioning
confidence: 99%
“…[24,25] GAA gene expression has been found to be speci cally increased in CAD patients than in controls. [26] CARD14, which is mainly associated with psoriasis (ongoing clinical studies suggest increased risk of CVDs in psoriasis) and auto-in ammatory disorders, acts as a pro-in ammatory gene by affecting NF-kB activation in the IL-17 in ammation pathway. Puig et al [27] found that expression of genes such as CARD14 classi ed human atherosclerotic plaque by relative in ammation status.…”
Section: Discussionmentioning
confidence: 99%